Breast Cancer Subtypes among Iraqi Patients: Identified By Their ER, PR and HER2 Status - Alwan, Nada A.S.; Tawfeeq, Furat N.; Muallah, Faisal H. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: Breast cancer ranks the first among the Iraqi population since three decades and is currently forming a major public health problem being the second cause of death women. Novel management of breast cancer depends upon precise evaluation of their molecular subtypes; identified by Hormone (Estrogen and Progesterone) receptors and HER2 contents of the primary tumor.Objective: To assess the rates of the different molecular breast cancer subtypes in the examined tissue specimens belonging to females diagnosed with breast cancer in Iraq; correlating the findings with those reported in the literature at the regional and global levels.Patients and Methods: This retrospective study documented the findings of tissue biopsy examination belonging to 686 female patients diagnosed with breast cancer. Formalin fixed paraffin-embedded blocks were utilized to assess the availability of Estrogen receptors (ER), Progesterone receptors (PR) and HER2 expressions through semi quantitative immuno-histochemical staining technique. Breast carcinomas were classified into four main molecular subtypes: Luminal A: ER/PR(+) / HER2(-), Luminal B/Triple Positive: ER/PR(+) / HER2(+), Non-Luminal HER-2 enriched: ER/PR(-) / HER2(+) and Non-Luminal/Triple Negative: ER/PR(-) and HER2(-). Other phenotypes included: ER(+)/PR(-) / HER2(+), ER(-)/PR(+) / HER2 (+), ER (+)/PR (-) / HER2 (-) and ER (-)/PR (+) / HER2 (-).Results: Out of the exanimated cases of breast carcinomas, the registered rates of positive ER, PR and HER2 tumor contents in this study were 67.8%, 65.3% and 29.4% respectively. The main identified phenotype was the Luminal A in 309 cases (45%). That was followed by the Triple Negative in 107 cases (15.6%) and Triple Positive/Luminal B (96 cases, 14%), while 71 cases (10.3%) were HER2 enriched. The corresponding rates of the (E+/P-/H+), (E-/P+/H+), (E+/P-/H-) and (E-/P+/H-) subtypes were 3.1%, 2.0%., 5.7% and 4.2% respectively. Differences in in the expressions of these IHC molecular markers are illustrated among different countries.Conclusions: Due to the displayed variations in the socio-demographic characteristics and biological risk factors among patients in different populations, it is mandatory to identify the molecular marker subtypes of breast cancer expressions in order to assess the impact of management and response to therapy. The routine documentation of their patterns in the cancer registry reports and published research ensures the validity and reliability of the presented clinical data.الخلفية: سرطان الثدي يحتل المرتبة الأولى بين السكان العراقيين منذ ثلاثة عقود، ويشكل حاليا مشكلة صحية رئيسية حيث يعتبر السبب الثاني للوفاة عند النساء. تعتمد أسس العلاج الجديدة لسرطان الثدي على التقييم الدقيق لأنواعها الفرعية الجزيئية و التي تحددها مستويات مستقبلات هرمون (الاستروجين والبروجسترون) ومحتويات  HER2 في الورم الرئيسي.الهدف من الدراسة: تقييم معدلات مختلف الأنواع الفرعية لسرطان الثدي الجزيئي في عينات الأنسجة التي تم فحصها والتي تخص الإناث المصابات بسرطان الثدي في العراق؛ وربط النتائج مع تلك المسجلة على الصعيدين الإقليمي والعالميالمرضى والطرق: وثقت هذه الدراسة بأثر رجعي نتائج فحص خزعة الأنسجة التي تنتمي إلى 686 مريضة مشخصة بسرطان الثدي. واستخدمت لتقييم توافر مستقبلات الاستروجين (ER)، مستقبلات البروجسترون (PR) والتعبيرات HER2 من خلال تقنية الطيخ المناعي شبه الكمي. تم تصنيف سرطان الثدي إلى أربعة أنواع فرعية جزيئية رئيسية: Luminal A:  ER/PR(+) / HER2(-), Luminal B/Triple Positive:    ER/PR(+) / HER2(+), Non-Luminal HER-2 enriched: ER/PR(-) / HER2(+) and Non-Luminal/Triple Negative:   ER/PR(-) and HER2(-). و انواع اخرى ER(+)/PR(-) / HER2(+), ER(-)/PR(+) / HER2 (+), ER (+)/PR (-)  / HER2 (-) and ER (-)/PR (+) / HER2 (-).النتائج: من بين حالات سرطان الثدي المهددة، كانت المعدلات المسجلة لمحتوى الأورام الموجبة ER, PR و   HER2 في هذه الدراسة 67.8٪ و 65.3٪ و 29.4٪ على التوالي. وكان النمط الظاهري المحدد الرئيسي اللمعية A في 309 حالات (45٪). وأعقب ذلك السلبي الثلاثي في 107 حالات (15.6٪) وثلاثية إيجابية / لومينال B (96 حالة، 14٪)، في حين أن 71 حالة (10.3٪) كانت HER2 المخصب. وكانت المعدلات المقابلة من (E + / P- / H +)، (E / P + / H +)، (E + / P- / H-) و (E / P + / H-) فرعية 3.1٪، 2.0٪. ،   و 5.7٪ و 4.2٪ على التوالي. وتظهر الاختلافات في التعبير عن هذه العلامات الجزيئية بين مختلف البلدان.الاستنتاجات والتوصيات: نظرا للاختلافات المعروضة في الخصائص الاجتماعية الديموغرافية وعوامل الخطر البيولوجية بين المرضى في مختلف السكان، فمن الضروري تحديد الأنواع الفرعية الجزيئية من تعبيرات سرطان الثدي من أجل تقييم تأثير الاستجابة للعلاج . ان التوثيق الروتيني لأنماط سرطان الثدي في تقارير سجل السرطان والبحوث المنشورة يضمن صحة ودقة البيانات السريرية ذات العلاقة.